An investigation into the influence of rooibos (Aspalathus linearis) on androgen metabolism in normal and prostate cancer cells - Du Toit, Therina (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.